An integrated model for fire sales and default contagion - Nils Detering; Thilo Meyer-Brandis; Konstantinos Panagiotou; Daniel Ritter (Mathematics and Financial Economics, 2020)
Fire sales and default contagion are two of the main drivers of systemic risk in financial networks. While default contagion spreads via direct balance sheet exposures between institutions, fire sales describe iterated distressed selling of assets and their associated decline in price which impacts all institutions invested in these assets. That is, institutions are indirectly linked if they have overlapping asset portfolios. In this paper, we develop a model that helps us understand the joint effect of the two contagion channels and investigate structures of financial systems that promote or hinder the spread of an initial local shock. We first consider the contagion process for an explicitly given system and then derive our main results for random ensembles of systems whose macroscopic statistical characteristics of defining parameters are close to each other. In particular, we model direct exposures by means of a random graph. Our approach ensures robustness to local uncertainties and changes in the system. We characterize resilient and non-resilient system structures by criteria that can be used by regulators to assess system stability. Moreover, we provide explicit capital requirements that secure the financial system against the joint impact of fire sales and default contagion.
Keywords: C02; E61; G01; 330; Systemic risk; Financial contagion; Asset fire sales; Price-mediated contagion; Default contagion; Capital requirements